MENTORING AS A FORM OF ADAPTATION OF CIVIL SERVANTS - M. Krutzova (Вестник университета)
The article deals with the introduction of mentoring into civil service system. The aims for adaptation of a civil servant are set. The function of adaptation is allocated between the mentor and the personnel department of public authority. Legal bases of introduction of mentoring into the public service, the purposes and principles of mentoring as well as motivation of teachers and the criteria for evaluation of the mentor are presented. The results of the survey of public servants on the relevance and effectiveness of mentoring in the public service are briefly explained.